Twórczość Jakowa Gołosowkera w kontekście kultury rosyjskiej i zachodnioeuropejskiej - Biełousowa, Wiera (Studia Rossica Posnaniensia, 2012)
The aim of the present article is to open up the connection of Jakov Golosovker’s creativity with Russian and Western European culture (the Silver Age, Antique culture, German romanticism, German philosophy).